(untitled) (Scientific journal of the Fergana State University, 2024)
The article gives information about the specific features and perspectives of teaching English to students of the Faculty of Geology. Geology students often face unique linguistic, cognitive, and cultural demands in their academic and professional work. The study of geology texts, the use of academic terminology and grammar, the development of critical thinking and scientific thinking skills, and other related topics are the main subjects studied. The article concludes by highlighting the value of incorporating student-centered, high-tech teaching methods, as well as the importance of creating a supportive learning environment that values diversity and encourages interdisciplinary collaboration.